Dielectric engineering of Ge nanocrystal/SiO2 nanocomposite thin films with Ge ion implantation: Modeling and measurement. (15th October 2015) - Liu, Zhen; Yang, Ming; Chen, T.P.; Liu, Yang; Zhang, Hai Yan
Graphical abstract: Highlights: Ion implantation technique is used to synthesize nc-Ge/SiO2 nanocomposite thin films. A sublayer model is proposed to obtain effective dielectric constant and capacitance. Distributions and reduced dielectric constant of nc-Ge are considered in modeling. Modeled capacitances agree well with experimental values from C – V measurements. Dielectric engineering of nc-Ge/SiO2 nanocomposite is realized by ion implantation. Abstract: Ge nanocrystal (nc-Ge) embedded SiO2 nanocomposite thin films have been synthesized with the ion implantation technique. The distribution profile of nc-Ge in the SiO2 matrix can be tailored by varying the implantation energy and dose in the Ge ion implantation process; thus the effective dielectric constant of the nc-Ge/SiO2 nanocomposite thin films can be engineered. The effective metal–oxide-semiconductor (MOS) capacitance of the nanocomposite thin films has been calculated using the sub-layer model and the Maxwell–Garnett effective medium approximation, taking the reduced dielectric constant corresponding to the nanometer size of nc-Ge into account. On the other hand, capacitance–voltage measurements on the MOS structures based on the nc-Ge/SiO2 thin films have been conducted to extract the capacitance experimentally. The modeling and measurement results have shown good agreement, suggesting that the nanocomposite dielectric engineering can be easily realized through the energy- and dose-controlled Ge + implantation technique.